奈米電子束微影技術探索新奇現象-無序過濾器、人造原子、Luttinger液體與鐵磁奈米接觸點 - 簡紋濱; JIAN WEN-BIN (My University, 2012)
為延續並持續發展前期計畫之「探索準一維奈米接觸點與零維電子系統」與「耦合奈 米晶粒陣列之電子結構與光學特性」，我們提出利用電子束微影術，發展奈米奈米線與 凝膠奈米晶粒(半導體量子點)材料之奈米元件，藉由此元件技術發展，我們預期能探索 新奇物理現象。 在奈米線電子元件方面，本實驗室累積長期經營的經驗與技術，能控制金屬電極/半導 體奈米線間之接觸介面，前期一方面將利用無序介面，製做電子能量濾波器，用來影 響半導體奈米線對光或氣體分子等的感測反應，另一方面將利用金屬/半導體介面之電 場，壓縮奈米線內電子系統的維度，由三維電子系統轉變為一維電子系統，並可能顯 現出Luttinger liquid 行為。後期使用本實驗室新組裝完成之磁性薄膜成長系統，在奈 米線上製做鐵磁性金屬電極，除可探討自旋電子傳輸行為，更進一步要觀察金半無序 介面、一維電子系統與自旋電子在此奈米自旋電子元件上互相影響及各自所展現的行 為。 在凝膠奈米晶粒電子元件方面，本實驗室能製做奈米間隙的兩電極，間隙寬度小到十 奈米，且有用低溫(5 K)掃描穿隧電流顯微鏡(STM)探索人造原子經驗，前期將製造單 奈米晶粒電子元件，除可製做室溫單電子電晶體，更可在低溫下探索人造原子之電子 態，雙奈米晶粒元件之耦合電子態。後期用此奈米間隙技術發展分子電子元件，並製 做鐵磁金屬奈米接觸點元件，探索自旋電子穿隧行為。

To extends our previous NSC programs: “Exploring Quasi-One-Dimensional Nanocontact and Zero-Dimensional Electron System” and “Electrical and Optical Properties of Assembled Nanocrystal Arrays”, we propose to develop nanoelectronic devices based on semiconductor nanowires and nanocrystals (quantum dots) using the electron-beam lithography technique. With this experimental nano approach, we expect to discover and explore novel physical phenomena. Physics coming with nanodevices of nanowires and nanocrystals are described separately as follows. In the past years, we developed techniques not only for deposition of metal electrodes onto semiconductor nanowires but also for engineering the nanocontact at the interface of metal electrode/semiconductor nanowire. In the beginning, we will adopt this technique to develop a quantum, disorder filter which can be applied to an enhancement of sensibility for photoand gas-sensors. In addition, we will engineer the Schottky contact at the interface of metal/semiconductor nanowires to deplete carriers inside the nanowires. Thus, this nanowire confined electron system could exhibit Luttinger-liquid behaviors of a particular one-dimensional electron system. On the other hand, a sputtering system for the deposition of ferromagnetic materials has been setup in our laboratory. We will go forward to deposit ferromagnetic metals as contact electrodes on semiconductor nanowires. These nanowire spintronic devices provide a platform for learning the spin-dependent transport and, moreover, the interplay among the disorder interface, the one-dimensional electron system, and the electron spin. We have fruitful research results and experiences in the field of investigating electronic structures of artificial atoms (semiconductor nanocrystals or quantum dots) by low-temperature scanning tunneling microscopy (LTSTM) at 5 K. We are still working in this field in cooperation with theorists to uncover more interesting physics. The LTSTM image data are, however, difficult to be acquired. We therefore turn to fabricate single nanocrystal devices for further studies. During the past three months, we have developed a technique to pattern a nanogap with ~10 nm in width between two metal electrodes. Moreover, we have the ability to position nanocrystals in the nanogap. As a first step, we will fabricate single nanocrystal devices for studies of not only the single electron tunneling at room temperature but also the quantum confined electron states (artificial atom states) at ~4 K. The coupling among few nanocrystals can also be learned and the experimental results will be compared with theoretical calculations. For the next step, we will further reduce the nanogap width to achieve a separation distance of ~1 nm so as to make molecular electronics. Additionally, we will utilize ferromagnetic metal as two separated metal electrodes to study spin dependent tunneling effects. In short, we will push our nanotechnology to the limit by using the electron-beam lithography. We will engineer the nanocontact at the interface of metal/semiconductor nanowire and we will develop a nanogap with a width of 1-10 nm. Using these nanotechnological approaches, we can explore disorder effects of hopping transport, artificial atom states, one-dimensional electron systems, Luttinger liquid, and ferromagnetic nanocontact. We expect to discover some new phenomena for design of new electronic functions for nanoelectronic devices.
Nano and Electron-Beam Lithography Approach to Discovery of Novel Phenomena – Disorder Filter, Artificial Atom, Luttinger Liquid, and Ferromagnetic Nanocontact
Keywords: 奈米接觸點; 單電子電晶體; 拉丁格液體; 奈米線自旋電子元件; 磁奈米接觸點; nanocontact; single electron transistor; Luttinger liquid; nanowire spintronics; magneto-nanocontact